2009
DOI: 10.1073/pnas.0900969106
|View full text |Cite
|
Sign up to set email alerts
|

Antigen storage compartments in mature dendritic cells facilitate prolonged cytotoxic T lymphocyte cross-priming capacity

Abstract: Dendritic cells (DCs) are crucial for priming of naive CD8 ؉ T lymphocytes to exogenous antigens, so-called ''cross-priming.'' We report that exogenous protein antigen can be conserved for several days in mature DCs, coinciding with strong cytotoxic T lymphocyte crosspriming potency in vivo. After MHC class I peptide elution, protein antigen-derived peptide presentation is efficiently restored, indicating the presence of an intracellular antigen depot. We characterized this depot as a lysosome-like organelle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
124
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 39 publications
16
124
1
Order By: Relevance
“…31 In ovalbumin cross-presentation by mouse DC systems, data collectively suggests that processing may occur in either the endosomal or cytosolic/proteasomal pathway, depending on the endocytic route taken (ie, choice of binding to endocytic receptors) and configuration of the antigen (ie, soluble or particulate). 4,15,28,32,33 Our data in human MoDCs now shows that for HCMV pp65, Fc␥R-mediated uptake potentiates crosspresentation in a manner that requires processing both in the endosomal pathway and by the proteasome. Earlier flow cytometrybased work suggested that Fc␥R are not expressed on BDCA-3 ϩ DCs found in PBMCs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…31 In ovalbumin cross-presentation by mouse DC systems, data collectively suggests that processing may occur in either the endosomal or cytosolic/proteasomal pathway, depending on the endocytic route taken (ie, choice of binding to endocytic receptors) and configuration of the antigen (ie, soluble or particulate). 4,15,28,32,33 Our data in human MoDCs now shows that for HCMV pp65, Fc␥R-mediated uptake potentiates crosspresentation in a manner that requires processing both in the endosomal pathway and by the proteasome. Earlier flow cytometrybased work suggested that Fc␥R are not expressed on BDCA-3 ϩ DCs found in PBMCs.…”
Section: Discussionmentioning
confidence: 63%
“…28 For immune complexes, the requirements for endosomal processing and proteasome-mediated peptide generation are not fully clear, particularly for human myeloid DCs. 3,29 We therefore assessed in human MoDCs the role of antigen processing in the endosomal pathway and by the proteasome.…”
Section: Cross-presentation Of Fc␥r-targeted Viral Antigen Requires Amentioning
confidence: 99%
“…Prolonged antigen storage favors MHC I cross-presentation as it facilitates antigen transfer to the cytosol, rather than its rapid degradation in the lysosomes. 44,45 Indeed, LAP, the process by which LC3 is recruited to phagosomes, has recently been implicated in promoting antigen stability in DC 46 unlike in other cell types where it is proposed to enhance antigen degradation. 21,22,47 This autophagy-dependent mechanism could be of more importance for soluble antigen that is likely to be more rapidly degraded than cell-associated antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be envisaged that for an effective in vivo expansion of RSV-specific CD4 + and CD8 + T cells, indirect routes of Ag presentation are most effective for efficient induction of T cell responses whereby DC acquire noninfectious material like opsonized virus particles or necrotic infected cells. Cross presentation is facilitated by stimulation of innate immune receptors expressed by DCs (56)(57)(58)(59)(60). The efficacy of the cross presentation route via MHC class I molecules and the relative contribution of MHC class II presentation for in vivo RSV-specific T cell activation might depend on several factors.…”
Section: Discussionmentioning
confidence: 99%